The mediating role of human capital on the relationship between staffꞌs self-leadership and school's organizational agility - سیدمحمد میرکمالی; کبری خباره; ابراهیم مزاری; یونس رومیانی (Allameh Tabataba'i University Press, 2015)
This study aimed to explain the mediating role of human capital on the relationship between stuff's self-leadership and school's organizational agility. The research method was descriptive and correlational and data analysis method was SEM. The population consists of all administrators, principals, teachers and administrative staff first and second elementary school area of Rey that Using Cochran's sampling formula that Sample size was determined 170 persons by Stratified sampling with proportional allocation. For data collection used of self-leadership questionnaire of Abili and Mazari (2014) with the reliability (α =0/95), human capital questionnaire of Naderi (2011) with the reliability (α=0/97) and organizational agility questionnaire of Moradi (2013) with the reliability (α =0/96) for analyzing data Kolmogorov-Smirnov test, one sample t-test, stepwise regression and structural equation modeling was used. Results showed that self-leadership, human capital and organizational agility are higher than average. The correlation results showed that three variables correlate with each other this have significant relationship (p <0/01). Structural equation modeling showed that self-leadership (γ=0/60) on human capital and HC (β=0/81) on organizational agility have impact. Also self-leadership indirectly and with Mediating of HC impact on organizational agility (γ=0/39) but have not directly impact on organizational agility. It can be concluded that self-responsibility and self-initiate-based behaviors such as self-leadership, provides not only growth human capital, but also facilitate organizational agility through human capital.